2022
DOI: 10.3233/wor-220062
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic-related anxiety, stress, and depression among teachers: A systematic review and meta-analysis

Abstract: BACKGROUND: As millions of teachers have been forced to rely upon remote teaching due to the closure of schools during the COVID-19 pandemic. It is particularly important to understand the extent to which teacher’s psychological wellbeing has been affected by this global health crisis. OBJECTIVE: The aim of this comprehensive systematic review and meta-analysis was twofold: 1) ascertain the prevalence of stress, anxiety, depression among teachers during the COVID-19 outbreak; 2) identify the associated factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 99 publications
3
29
0
2
Order By: Relevance
“…Socio-demographic, school and work-related factors are all associated with both anxiety and depression [ 42 , 50 , 51 , 80 ]. This association is consistent with what was reported in a systematic review and meta-analysis by Ma et al, which suggested that teachers’ experiences of psychological issues were associated with various socio-demographic factors such as gender, institutional factors, teaching experience, and workload volume [ 100 ]. In this scoping review, conflicting results were found in relation to the association between teacher gender and depression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Socio-demographic, school and work-related factors are all associated with both anxiety and depression [ 42 , 50 , 51 , 80 ]. This association is consistent with what was reported in a systematic review and meta-analysis by Ma et al, which suggested that teachers’ experiences of psychological issues were associated with various socio-demographic factors such as gender, institutional factors, teaching experience, and workload volume [ 100 ]. In this scoping review, conflicting results were found in relation to the association between teacher gender and depression.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalences of stress, burnout, anxiety and depression reported in this scoping review are similar to those reported in two systematic reviews and meta-analysis conducted among teachers during the pandemic. For example, the prevalence of stress reported by Ma et al, from a meta-analysis of 54 studies was 62.6%, whereas the prevalence of anxiety was 36.3% and depression was 59.9% among teachers during the pandemic [ 100 ]. In another meta-analysis, the prevalence range of anxiety was 10% to 49.4%; depression was 15.9% to 28.9%; and stress was 12.6% to 50.6% [ 101 ], which all fall within the range reported in this scoping review for stress [ 28 , 40 ], anxiety [ 42 , 56 ], and depression [ 48 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, high expectations and work demands were the most common stressors before and during the pandemic. Similarly, Ma et al ( 2022 ) found that workload and sense of organizational unfairness were consistently high stressors across world contexts. In Iran, these teacher stressors have been common for at least the past decade (Ghasemi, 2022b ).…”
Section: Discussionmentioning
confidence: 89%
“…Most of the literature on teacher stress and coping to date has focused on Western educational contexts. Yet available data suggest that teachers in other world contexts also experience high levels of stress and burnout and many of the same common stressors (Ma et al, 2022 ). For instance, Ma et al ( 2022 ) recently completed a meta-analysis of 64 studies in 22 countries that were conducted during the pandemic and found high levels of stress across nations.…”
Section: Teacher Stress In An Iranian Contextmentioning
confidence: 99%
See 1 more Smart Citation